2013
DOI: 10.4300/jgme-d-12-00343.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Simulation Training on Time to Initiation of Cardiopulmonary Resuscitation for First-Year Pediatrics Residents

Abstract: A simulation-based educational intervention significantly reduced time to initiation of CPR for first-year pediatrics residents. Simulation training facilitated acquisition of critical CPR skills that have the potential to impact patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“… 8 , 10 Simulation-based education interventions reduce the time to call for help, initiate bag-mask ventilation (BVM), and start CPR for first-year pediatric residents. 11 Participants and observants in mock code programs have also reported increased self-confidence and comfort with knowledge during a code, as well as decreased anxiety. 12 , 13 Promisingly, an increased number of mock codes at one tertiary care academic medical center has been associated with improved survival rates from 33% to 50% in pediatric cardiopulmonary arrests.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 10 Simulation-based education interventions reduce the time to call for help, initiate bag-mask ventilation (BVM), and start CPR for first-year pediatric residents. 11 Participants and observants in mock code programs have also reported increased self-confidence and comfort with knowledge during a code, as well as decreased anxiety. 12 , 13 Promisingly, an increased number of mock codes at one tertiary care academic medical center has been associated with improved survival rates from 33% to 50% in pediatric cardiopulmonary arrests.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation has been used in many settings to teach students and residents resuscitation skills. Simulation-based educational interventions have been shown to improve resident knowledge and performance in studies assessing simulation for neonatal and pediatric resuscitations [5–7], pediatric airway management [8], and time to initiation of CPR [9]. While these studies were conducted on high-fidelity simulators, there is also evidence that low-fidelity simulation can be effective, and that the transfer of learning is not dependent on the simulator fidelity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the results in this study showed a significant improvement in team performance represented by a decrease in CPR initiation time after the mock code simulation program, in both the CRP initiation time analysis and the AHA adherence analysis, as both revealed faster CPR initiation, which may reflect that cardiac arrest recognition improved after the mock code simulation program, and the first responders initiated chest compression earlier. Other studies reported the same results related to the CPR initiation time, which was part of the team dynamics improvement in some of them [21,25,29]. In our study, we did not find significant changes in the survival rate after the mock code simulation program, but the small sample size, which is one of the major study limitations, may have affected the results and made these changes difficult to trace, while the results of other studies showed better outcomes after implementing mock code simulation programs [30].…”
Section: Discussionmentioning
confidence: 58%
“…Several studies support the use of resuscitation training programs that are multidisciplinary sessions based on the latest resuscitation guidelines. Furthermore, mock code training programs minimize performance differences and help to improve the response time from the onset of loss of pulse to the initiation of chest compressions, the time spent administering the first dose of epinephrine, and defibrillation time [13,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%